The prevalence of proximal fractures of dental crowns with amalgam fillings - Pandurić, Vlatko (Array, 2009)
Abstract: The purpose of this paper was to determine the prevalence and impact of various etiological factors on marginal ridge fractures of teeth with amalgam fillings. 50 subjects participated in this research, 172 teeth restored with amalgam were examined out of which 28 premolars and 144 molars of both jaws. Data used in the research was obtained by nonaggressive exploration of oral cavity and by checking dental charts and radiographic charts of patients. Patients were divided in three gendered age groups. Etiological factors used in the research were: the position of teeth in jaws, classification of amalgam fillings according to Black, the duration of fillings, the presence of caries on proximal surfaces not included in restoration and tooth vitality. Also, Angle Class, habits and presence of fixed prosthetic appliances in opposite jaw were taken into consideration. Results for each patient were separately written in the questionnaire. Statistical analysis was carried out by Pearson’s c2-test. According to obtained results 51% of teeth with amalgam fillings have a fracture of marginal ridge. Statistically significant factors that influenced the occurrence of fractures of proximal surfaces in this research were classification of amalgam fillings according to Black, the patient’s age and the existence of caries on proximal surface